Antitissue transglutaminase antibodies' normalization after starting a gluten-free diet in a large population of celiac children-a real-life experience. Issue 3 (March 2022) - Sbravati, Francesca; Cosentino, Anita; Lenzi, Jacopo; Fiorentino, Michelangelo; Ambrosi, Francesca; Salerno, Angela; Di Biase, Annarita; Righi, Beatrice; Brusa, Sandra; Valin, Paola Sogno; Bruni, Laura; Battistini, Barbara; et al.
Abstract: Introduction: Few data are available regarding the trend of IgA anti-transglutaminase antibodies (TGA-IgA) in children with celiac disease (CD) on a gluten-free diet (GFD). Our aim is to examine the normalization time of CD serology in a large pediatric population, and its predictors. Material and methods: We retrospectively evaluated the normalization time of TGA-IgA and its predictive factors (age, sex, ethnicity, symptoms, associated diabetes/thyroiditis, Marsh stage, TGA-IgA and endomysial antibody levels at diagnosis, diet adherence), in 1024 children diagnosed from 2000 to 2019 in three pediatric Italian centers, on a GFD. Results: TGA-IgA remission was reached in 67, 3%, 80, 7%, 89, 8% and 94, 9% after 12, 18, 24 and 36 months from starting a GFD, respectively (median time = 9 months). TGA-IgA >10´upper limit of normal at diagnosis (HR = 0.56), age 7–12 years old (HR = 0.83), poor compliance to diet (HR = 0.69), female sex (HR = 0.82), non-Caucasian ethnicity (HR = 0.75), and comorbidities (HR = 0.72) were independent factors significantly associated with longer time to normalization. Conclusions: Our population is the largest in the literature, with the majority of patients normalizing CD serology within 24 months from starting a GFD. We suggest a special attention to patients with comorbidities, language barriers or age 7–12 years for a proper management and follow-up.